Fungal Origins of the Bicyclo[2.2.2]diazaoctane Ring System of Prenylated Indole Alkaloids - Finefield, Jennifer M. (2012)
Over eight different families of natural products, consisting of nearly seventy secondary metabolites, which contain the bicyclo[2.2.2]diazaoctane ring system, have been isolated from various Aspergillus, Penicillium, and Malbranchea species. Since 1968, these secondary metabolites have been the focus of numerous biogenetic, synthetic, taxonomic, and biological studies, and, as such, have made a lasting impact across multiple scientific disciplines. This review covers the isolation, biosynthesis, and biological activity of these unique secondary metabolites containing the bridging bicyclo[2.2.2]diazaoctane ring system. Furthermore, the diverse fungal origin of these natural products is closely examined and, in many cases, updated to reflect the currently accepted fungal taxonomy.